2003
DOI: 10.1016/s0166-3542(03)00003-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic transformation of AZTp4A by Ap4A hydrolase regenerates AZT triphosphate

Abstract: The reverse transcriptase (RT) of HIV which has been inhibited by the incorporation of AZT into the primer strand is subject to a deblocking reaction by cellular ATP. This reaction yields unblocked primer plus the dinucleoside tetraphosphate, AZTp 4 A. In the present study, we report that AZTp 4 A is an excellent substrate for the enzyme Ap 4 A hydrolase (asymmetrical dinucleoside tetraphosphatase, EC 3.6.1.17), an enzyme that is widely distributed in many cell types. Progress of the reaction has been monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…ATP might thus be a preferred excision substrate for TAM-RT since the reaction could lead to irreversible removal of 3′-terminal AZTMP as the novel product AZTp4A. While the cellular enzyme Ap4A hydro-lase (asymmetrical dinucleoside tetraphosphatase) catalyzes the hydrolysis of AZTp4A resulting in the regeneration of AZTTP in many cell types (25), this reaction would occur away from the RT active site and thus the newly formed AZTTP would not be immediately available for reincorporation into the growing viral DNA. Victorova et al (15) previously showed that HIV RT can use some bis(2′deoxynucleoside)-5′,5′-tetraphosphates as substrates for DNA polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…ATP might thus be a preferred excision substrate for TAM-RT since the reaction could lead to irreversible removal of 3′-terminal AZTMP as the novel product AZTp4A. While the cellular enzyme Ap4A hydro-lase (asymmetrical dinucleoside tetraphosphatase) catalyzes the hydrolysis of AZTp4A resulting in the regeneration of AZTTP in many cell types (25), this reaction would occur away from the RT active site and thus the newly formed AZTTP would not be immediately available for reincorporation into the growing viral DNA. Victorova et al (15) previously showed that HIV RT can use some bis(2′deoxynucleoside)-5′,5′-tetraphosphates as substrates for DNA polymerization.…”
Section: Discussionmentioning
confidence: 99%